2022
DOI: 10.3389/frsfm.2022.1035377
|View full text |Cite
|
Sign up to set email alerts
|

Untangling effects of proteins as stabilizers for foam films

Abstract: Foam film’s properties have a high impact on the properties of the macroscopic foams. This work focusses on protein stabilized foam films. The direct comparison of three different proteins with a concentration normalized to the protein surface enables to distinguish between electrostatic, steric and network stabilization effects. In order to untangle those effects, we study and compare two globular proteins (β − lactoglobulin, BLG, and bovine serum albumin, BSA) and a disordered, flexible protein (whole casein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Proteins are one of the most important food ingredients that adsorb at the air/solution interface and thereby create stabilizing films around bubbles in foam [6]. These layers also increase the visco-elastic properties of the foam film surfaces and help to stabilize them [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins are one of the most important food ingredients that adsorb at the air/solution interface and thereby create stabilizing films around bubbles in foam [6]. These layers also increase the visco-elastic properties of the foam film surfaces and help to stabilize them [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the foaming properties can be altered by protein hydrolysis or by enhancing the proteins' tendency to aggregate [10,11]. It has also been shown that higher foam stability is provided by globular proteins because of their capacity to form visco-elastic networks at aqueous solution surfaces [7,12].…”
Section: Introductionmentioning
confidence: 99%